Moral distress: challenges for an autonomous nursing professional practice - Edison Luiz Devos Barlem; Valéria Lerch Lunardi; Jamila Geri Tomaschewski; Guilherme Lerch Lunardi; Wilson Danilo Lunardi Filho; Camila Rose Guadalupe Barcelos Schwonke
Constantly experiencing limiting situations that hinder a professional practice coherent with its principles - of autonomy and advocacy of users' interests -, and often conditioned to experience moral distress, the nursing profession plays a prominent role in the current health model because it has the characteristic of managing the care rendered to users in a perspective of social inclusion, both in the basic health network and in hospitals. Aiming at carrying out a reflection on the nursing practice and the difficulties present in its work routine, and considering its characteristics as a profession, this article sought to make a reflection between the practice of nursing and the numerous moral challenges imposed by the routine, resulting, in many cases, in a value crisis that can reverberate directly on the quality of the service rendered, and in abandonment of the ideals of advocacy for users.